A computational study on plasticity during theta cycles at Schaffer collateral synapses on CA1 pyramidal cells in the hippocampus. Issue 2 (25th September 2014) - Saudargiene, Ausra; Cobb, Stuart; Graham, Bruce P.
ABSTRACT Cellular activity in the CA1 area of the hippocampus waxes and wanes at theta frequency (4–8 Hz) during exploratory behavior of rats. Perisomatic inhibition onto pyramidal cells tends to be strongest out of phase with pyramidal cell activity, whereas dendritic inhibition is strongest in phase with pyramidal cell activity. Synaptic plasticity also varies across the theta cycle, from strong long‐term potentiation (LTP) to long‐term depression (LTD), putatively corresponding to encoding and retrieval phases for information patterns encoded by pyramidal cell activity (Hasselmo et al. (2002a) Neural Comput 14:793–817). The mechanisms underpinning the phasic changes in plasticity are not clear, but it is likely that inhibition plays a role by affecting levels of electrical activity and calcium concentration at synapses. We explore the properties of synaptic plasticity during theta at Schaffer collateral synapses on CA1 pyramidal neurons and the influence of spatially and temporally targeted inhibition using a detailed multicompartmental model of the CA1 pyramidal neuron microcircuit and a phenomenological model of synaptic plasticity. The results suggest CA3‐CA1 synapses are potentiated on one phase of theta due to high calcium levels provided by paired weak CA3 and layer III entorhinal cortex (EC) inputs even when somatic spiking is inhibited by perisomatic interneuron activity. Weak CA3 inputs alone induce lower calcium transients and result in depression of the CA3‐CA1 synapses. These synapses are depressed if activated in phase with dendritic inhibition as strong CA3 inputs alone are not able to cause high calcium in this theta phase even though the CA1 pyramidal neuron shows somatic spiking. Dendritic inhibition acts as a switch that prevents LTP and promotes LTD during the retrieval phases of the theta rhythm in CA1 pyramidal cell. This may be important for not overly reinforcing recalled memories and in forgetting no longer relevant memories. © 2014 Wiley Periodicals, Inc.